2016
DOI: 10.1021/acs.chemmater.5b04411
|View full text |Cite
|
Sign up to set email alerts
|

Cu2ZnSnS4 Nanorods Doped with Tetrahedral, High Spin Transition Metal Ions: Mn2+, Co2+, and Ni2+

Abstract: Because of its useful optoelectronic properties and the relative abundance of its elements, the quaternary semiconductor Cu 2 ZnSnS 4 (CZTS) has garnered considerable interest in recent years. In this work, we dope divalent, high spin transition metal ions (M 2+ = Mn 2+ , Co 2+ , Ni 2+ ) into the tetrahedral Zn 2+ sites of wurtzite CZTS nanorods. The resulting Cu 2 M x Zn 1−x SnS 4 (CMTS) nanocrystals retain the hexagonal crystalline structure, elongated morphology, and broad visible light absorption profile o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 116 publications
2
30
0
Order By: Relevance
“…In literature, some reports can be found claiming kesterite as the crystal structure for Cu 2 MnSnS 4 . However, most studies assume that Cu 2 MnSnS 4 attains the stannite crystal structure based on results from neutron diffraction, where the stannite symmetry group Itrue4¯2m yields a slightly better fit to the neutron diffraction data compared to the kesterite symmetry group Itrue4¯.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, some reports can be found claiming kesterite as the crystal structure for Cu 2 MnSnS 4 . However, most studies assume that Cu 2 MnSnS 4 attains the stannite crystal structure based on results from neutron diffraction, where the stannite symmetry group Itrue4¯2m yields a slightly better fit to the neutron diffraction data compared to the kesterite symmetry group Itrue4¯.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, many other quaternary chalcogenides such as CCTS, CFTS, CMTS, CNTS and hybrids of quaternary chalcogenides with magnetic metals such as CZTS‐NiPt, CZTS‐CoPt etc. have been explored for emerging applications in magneto‐electrical devices ,,,…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…Electrodeposition furthermore can be used to study other promising growth modifier metals. In particular, Ni and Co could be studied, since they have been reported to modify the lattice constant and band gap of the CZTS and promote better band alignment at the Cd/CZTS interface [198][199][200]. Furthermore, cobalt and nickel can be co-electrodeposited from a citrate based solution owing to their suitable reduction potential in the Cu-Zn-Sn electrodeposition system as an alternative simple method to dope CZTS films [76,201,202].…”
Section: Future Workmentioning
confidence: 99%
“…Furthermore, cobalt and nickel can be co-electrodeposited from a citrate based solution owing to their suitable reduction potential in the Cu-Zn-Sn electrodeposition system as an alternative simple method to dope CZTS films [76,201,202]. Cobalt-containing Cu 2 Co x Zn 1-x SnS 4 and Cu 2 CoSnS 4 materials have been grown as nanofibers and nanorods before [198,203]; however, a low doping amount in CZTS films for the modification of CdS/CZTS band alignment has not been reported as yet. Nickel containing Cu 2 Ni x Zn 1-x SnS 4 and Cu 2 NiSnS 4 materials have been grown as a film, nanofiber and nanorods [198,199,203]; nevertheless none of these studies reported the photoelectrochemical or solar cell performance of these materials.…”
Section: Future Workmentioning
confidence: 99%
See 1 more Smart Citation